Parasitoid wasps as effective biological control agents - Zhi-zhi WANG; Yin-quan LIU; Min SHI; Jian-hua HUANG; Xue-xin CHEN (Journal of Integrative Agriculture)
Biological control (biocontrol) is a safe, sustainable approach that takes advantage of natural enemies such as predators, parasitic insects or pathogens to manage pests in agroecosystems. Parasitoid wasps, a very large evolutionary group of hymenopteran insects, are well-known biological control agents for arthropod pests in agricultural and forest ecosystems. Here, we summarize the recent progress on the application of parasitoid wasps in biocontrol in China for the last five years. These include species diversity of parasitoid wasps, identification of dominant parasitoid wasps associated with insect pests and biocontrol practices (three types of biological control, i.e., classical, augmentative and conservation biological control) in several Chinese agroecosystems. We then treat different mass-rearing and release technologies and the commercialization of several parasitoid wasp species. We also summarize other work that may have a potential use in biocontrol, including the effect of plant volatiles on parasitoids and recent advance in the molecular mechanisms underlying the host regulation by parasitoid wasps. Future research area and applied perspectives are also discussed, noting that advances in biocontrol technologies in Chinese agriculture informs research at the global level.